2015
DOI: 10.1021/nl504091v
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Rectifiers: A New Design Based on Asymmetric Anchoring Moieties

Abstract: The quest for a molecular rectifier is among the major challenges of molecular electronics. We introduce three simple rules to design an efficient rectifying molecule and demonstrate its functioning at the theoretical level, relying on the NEGF-DFT technique. The design rules notably require both the introduction of asymmetric anchoring moieties and a decoupling bridge. They lead to a new rectification mechanism based on the compression and control of the HOMO/LUMO gap by the electrode Fermi levels, arising fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
165
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 142 publications
(179 citation statements)
references
References 82 publications
13
165
1
Order By: Relevance
“…27 HLG reduction of organic molecules in metallic junctions has been previously attributed to Fermi level pinning of the molecular states when attached to metal electrodes. 10,22 Likewise, the HLG reduction of 4TPA-C 60 is attributed to Fermi level pinning of the HOMO and LUMO at the Au/thiolate and C 60 /Au interfaces respectively, which aligns the HOMO and LUMO independently of the isolated gas phase energy gap. The electronic response of the molecule to finite biases was then calculated within the NEGF-DFT framework (see Methology for details).…”
mentioning
confidence: 98%
See 3 more Smart Citations
“…27 HLG reduction of organic molecules in metallic junctions has been previously attributed to Fermi level pinning of the molecular states when attached to metal electrodes. 10,22 Likewise, the HLG reduction of 4TPA-C 60 is attributed to Fermi level pinning of the HOMO and LUMO at the Au/thiolate and C 60 /Au interfaces respectively, which aligns the HOMO and LUMO independently of the isolated gas phase energy gap. The electronic response of the molecule to finite biases was then calculated within the NEGF-DFT framework (see Methology for details).…”
mentioning
confidence: 98%
“…It is therefore advantageous to identify U-type systems which have rectifying properties inherent in their asymmetric molecular structure.160) utilizing both the U and S mechanisms. 10,11 Simulations showed that the HOMO and LUMO of their proposed molecule was asymmetrically coupled to opposing electrodes. The HOMO-LUMO gap (HLG) could thus be tuned by application of a potential difference across the molecule.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The metal-molecule hybridization energy should be made small though, so as not to conceal this asymmetry by level broadening. This situation parallels with design principles for standard tunneling diodes [71][72][73] . We apply the voltage in a symmetric manner, and for simplicity, we keep the levels fixed, independent of bias.…”
Section: Charge Rectificationmentioning
confidence: 80%